PENINGKATAN PARTISIPASI DAN HASIL BELAJAR SOSIOLOGI MELALUI PEMBELAJARAN KOOPERATIF TIPE TEAM ACCELERATED LEARNING (TAL) DI SMAN 1 PLERET BANTUL - Retnani Sulistyowati (Ideguru: Jurnal Karya Ilmiah Guru, 2016)
The objectives of this study to improve partisipation and learning results of sociology throught applying cooperative learning type Team Accelerated Learning (TAL) at Senior High School 1, Pleret, Bantul, Yogyakarta. This Classroom Action Research has carried out on odd semester 2016/2017, on August until Septembre 2016, at SHS state 1 Pleret, Bantul. Data collection using observation instrument, student respond has measured by a questionnaire survey and interview, to measure learning result using pretest and posttest examination. Data analyzed using descriptive qualitatif to description the teaching learning of sociology using strategy cooperative type Team Accelerated Learning (TAL). The data show that: (1) TAL has effect to better teaching-learning process; (2) students’ learning in the classroom are assured and how they are cared by cooperative learning; (3) improved participation; (4) a dramatic change in student perception and eventually in attitude and perform. In conclusion: The strategy cooperative learning type Team Accelerated Learning (TAL), proved that TAL improving sociological science student’s competencies of Senior High School state 1 Pleret, Bantul, Yogyakarta, and also an effective to improve learning result of sociology.